The War in Ukraine: Implications for the Africa-Europe Peace and Security Partnership (The Strategic Review for Southern Africa, 2022)
This paper discusses the war in Ukraine and what the EU’s increasing preoccupation with it means for the EU-Africa peace and security partnership. It does this from the angle of a new EU funding mechanism, the European Peace Facility (EPF), which is a €5.6 billion fund that came into effect in March 2021 to support conflict management and international security during the EU’s seven-year budget period (2021 to 2027). The facility funds a variety of activities globally and—for the first time in the EU’s history— provides a legal basis for the EU to provide not only technical and material support but also lethal weapons to partner countries. As of May 2022, the EU has pledged to provide €2 billion to support Ukraine’s armed forces aside from the unprecedented economic sanctions the EU has imposed on Russia. The creation of the EPF is inspired by the EU’s ambitious Global Strategy of 2016 (EEAS 2016) and the preceding policy discourse between the EU and its member states on making the EU a “global player” and not just a “global payer”. This shift is partly a response to the emerging international geopolitical order in which the EU feels the need to assert itself and defend its interests globally. This marks a radical paradigm shift in EU foreign policy. The paper argues that the EU’s evolving foreign policy and its unforeseen use of EPF funds in Ukraine have at least two implications for Africa. First, the use of the EPF in Ukraine raises questions about the availability of funds for African peace support operations, which the EU has been supporting for some years. It raises also questions about the way Europe and Africa will decide about funding African security priorities. The EPF allows the transferring of funds and equipment to partner countries or regional coalitions directly, without the need to go through established regional organisations like the AU. Second, the EU’s changing security interests and geopolitical ambitions as well as Africa’s aspirations to find its place in the new global order could alter the dynamics of the EU-Africa peace and security partnership. While the EU remains an important economic and security actor in Africa—at the bilateral and continental levels—the EU-Africa partnership struggles to thrive and go beyond money to live up to its full potential. To meet their own aspirations, the paper argues that the AU and its member states will have to work harder to reduce their financial, security and economic dependence on non-African states. The AU and its member states will also have to avoid getting trapped in geopolitical confrontations between “the east” and “the west”. At the same time, they need to summon the political leadership the continent needs to prevent and manage internal political crises and conflicts on the continent while reducing interference from different international partners.
Keywords: European Union; Russia; War in Ukraine; Political Implications